Wind variability in the High Tatras Mountain - OSTROŽLÍK, Marián (Contributions to Geophysics and Geodesy, 2021)
Measurements and registration of the wind speed and wind direction are systematically carried out at the meteorological observatories Skalnaté Pleso and Stará Lesná, located in the High Tatras. Based on these measurements the seasonal variability of the wind speed and wind direction in the High Tatras region is studied. The different altitude, as well as the distinguished topographical conditions at both observatories enable to study the temporal variability of air circulation at two different altitudes. Anemographic records of the mean hourly wind speed and wind direction covering the period of the years 1992–2006 were used as an experimental basis. The methods of mathematical statistics were applied to the evaluation of these time series.